Factors affecting out of pocket health care expenditure among Sunanese households - Aamer B. M. Ghaleb; Aamer Basheir Mohammed Ghaleb (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012